# -5t+7t=h(t)

## Simple and best practice solution for -5t+7t=h(t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -5t+7t=h(t) equation:

Simplifying
-5t + 7t = h(t)

Combine like terms: -5t + 7t = 2t
2t = h(t)

Multiply h * t
2t = ht

Solving
2t = ht

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1ht' to each side of the equation.
-1ht + 2t = ht + -1ht

Combine like terms: ht + -1ht = 0
-1ht + 2t = 0

Factor out the Greatest Common Factor (GCF), 't'.
t(-1h + 2) = 0

Subproblem 1Set the factor 't' equal to zero and attempt to solve:

Simplifying
t = 0

Solving
t = 0

Move all terms containing t to the left, all other terms to the right.

Simplifying
t = 0
Subproblem 2Set the factor '(-1h + 2)' equal to zero and attempt to solve:

Simplifying
-1h + 2 = 0

Reorder the terms:
2 + -1h = 0

Solving
2 + -1h = 0

Move all terms containing t to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -1h = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -1h = 0 + -2
-1h = 0 + -2

Combine like terms: 0 + -2 = -2
-1h = -2

Add 'h' to each side of the equation.
-1h + h = -2 + h

Combine like terms: -1h + h = 0
0 = -2 + h

Simplifying
0 = -2 + h

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.Solutiont = {0}`